PENGARUH EDUKASI KEPATUHAN DIET DIABETES MELLITUS MELALUI SMARTPHONE TERHADAP KADAR GULA DARAH PASIEN DIABETES MELLITUS DI WILAYAH PUSKESMAS BONTANG UTARA 1 KOTA BONTANG - Puji Setio Wati; Tini, Tini; Lukman Nulhakim (Journal of Innovation Research and Knowledge, 2023)
Introduction: Diabetes Mellitus (DM) is one of the non-communicable diseases (NCDs) that is currently a global health threat. There are two risk factors for DM: non-modifiable ones such as age, gender, genetic factors, and modifiable factors such as lack of physical activity, diet, obesity, and dyslipidemia. In addition to focusing on treatment, controlling modifiable risk factors such as diet and physical activity is also very important so that blood sugar can be controlled. One way that can be done is to provide education about the DM diet. Media that can be used to provide education by utilizing smartphone technology. This study aims to determine the effect of DM diet compliance education through smartphones on blood sugar levels of DM patients in the work area of the North Bontang 1 Health Center. Methods: Type of quasi-experimental design research (Quasi Experiment Method). Pre test and post test design form nonequivalent control group sampling technique with Purposive Sampling as many as 22 people divided into 2 groups, namely the intervention group and the control group. The study was conducted by conducting a pre-test in both groups, then given DM diet education for the intervention group. Furthermore, the post test of blood sugar levels was carried out for both groups. Then the data were analyzed univariately and bivariately with the Paired Sample t-test and Independent Sample t-test. Results: In the intervention group, the results obtained sig. 0.000, so it can be concluded that there is a difference in fasting blood sugar levels before and after the intervention. While in the control group, the sig. 0.430, so it can be concluded that there is no difference in fasting blood sugar levels before and after in the control group. Conclusion: There are differences in blood sugar levels before and after educational interventions regarding the DM diet. It is recommended for the Puskesmas to hold education about the DM diet on a wider scale.